Effectiveness of pay it forward intervention compared to free and user-paid vaccinations on seasonal influenza vaccination among older adults across seven cities in China: study protocol of a three-arm cluster randomized controlled trial - Qing-Qing Li; Zizhen Huang; Jiangyun Chen; Junjie Wang; Duqiao Li; Xiaoshan Chen; Qing Zhao; Siyuan Liu; Wenjun He; Huanyuan Luo; Yuting Wan; Guangyu Tong; et al. (BMC Public Health)
Abstract Background Seasonal influenza poses an enormous burden worldwide, with older adults facing preventable morbidity and mortality. However, seasonal influenza vaccination coverage is poor among older populations in China. Pay-it-forward (giving a person a free vaccine and an opportunity to donate to support others) and financial incentives (e.g. free vaccination) could be effective in improving influenza vaccine uptake, but there are no prospective comparisons of these two strategies among older adults. The proposed study aims to compare the effectiveness of the pay-it-forward strategy in increasing influenza vaccination against free vaccination and user-paid vaccination among older adults in China. Methods This study is a three-arm cluster randomized controlled trial, which will be conducted in 21 community health centers across seven cities in China. A total of 1113 eligible older adults aged ≥ 60 years will be recruited. Three clusters in each city (total of 21 clusters in 7 cities) will be randomized into three arms in a 1:1:1 ratio, including (1) pay-it-forward arm: free vaccination and participants donate any amount of money to help other people; (2) free vaccination arm; and (3) standard-of-care arm (user-paid vaccination). The primary outcome is influenza vaccination verified by administrative records. Secondary outcomes include willingness to be vaccinated, willingness to donate, amount of donation, and incremental cost-effectiveness ratio. The primary outcome will be calculated for each arm and compared using one-way variance analysis. Discussion This study will examine the effectiveness of pay-it-forward strategy in comparison to the free vaccination and user-paid vaccination in improving influenza vaccination among older adults. Our findings will provide insights into better strategies for enhancing influenza vaccination, and support evidence-based policy decisions for promoting influenza vaccination. Trial registration Chinese Clinical Trial Registry (No. ChiCTR2400086840). Registered on 11 July 2024.